Safety and efficacy of toll-like receptor agonists as therapeutic agents and vaccine adjuvants for infectious diseases in animals: a systematic review - Oboge, Harriet; Riitho, V.; Nyamai, M.; Omondi, G.P.; Lacasta, Anna; Githaka, Naftaly W.; Nene, Vishvanath; Aboge, G.; Thumbi, S.M. (Frontiers Media, 2024)
Introduction: Strengthening global health security relies on adequate protection against infectious diseases through vaccination and treatment. Toll-like receptor (TLR) agonists exhibit properties that can enhance immune responses, making them potential therapeutic agents or vaccine adjuvants.